Interaction Between Dietary Lipid Level and Seasonal Temperature Changes in Gilthead Sea Bream Sparus aurata: Effects on Growth, Fat Deposition, Plasma Biochemistry, Digestive Enzyme Activity, and Gut Bacterial Community - Pelusio, Nicole Francesca; Scicchitano, Daniel; Parma, Luca; Dondi, Francesco; Brini, Elisa; D’Amico, Federica; Candela, Marco; Yúfera, Manuel; Gilannejad, Neda; Moyano, Francisco Javier; Gatta, Pier Paolo; Bonaldo, Alessio (Frontiers in Marine Science, 2021)
A 121-day feeding trial was undertaken to test the effects of two dietary lipid levels (16 and 21% L16, L21) in triplicated gilthead sea bream groups (initial weight: 67.5 g) reared at two different water temperatures (high, H 23°C and low, L 17°C) in the same recirculation system but exposed to a switch in temperature after 58 days. Fish kept at H were transferred to L (HL transition, autumn shift), and the fish kept at L were exposed to H (LH transition, summer shift), while continuing to receive the same diet to apparent satiation in each group. At the end of the trial, no significant diet effect on specific growth rate (SGR), feed intake (FI), and feed conversion rate (FCR) were detected in fish exposed to HL transition compared with those exposed to LH transition, while gross lipid efficiency (GLE) and lipid efficiency ratio (LER) were higher in L16. After temperature changes, L16 displayed higher SGR, FI, GLE, and LER, while mesenteric fat index was reduced. After temperature changes, the combined effects of low lipid diet and low temperature conditions resulted in higher pepsin activity, while trypsin, chymotrypsin, and lipase activities were generally higher at high lipid content. The combined effect of diet and temperature did not alter the metabolic plasma profile, except for the observed final higher aspartate aminotransferase (AST) and alkaline phosphatase (ALP) values when combining high dietary lipid (L21) and temperature changes. Different diets showed a significantly different gut microbiome layout, only at high temperature with L16 diet resulting in a higher load of Lactobacillus. On the contrary, no dietary impact on ecosystem diversity was observed, independently from the temperature. In addition, L16 diet in the HL transition favored an increase in Weissella and Bradyrhizobium genera in the gut microbiome, while in the final condition of LH transition, L21 diet favored a significant increase in Streptococcus and Bacillus. According to the results, the utilization of 16% dietary lipid levels in gilthead sea bream should be preferred during seasonal temperature changes in order to optimize feed utilization and gut health.